Estimativa do risco de contaminação por pesticidas na Sub-Bacia do Rio Moju, Mojuí dos Campos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The overconsumption of pesticides in the agricultural productive chain contributes significantly to environmental degradation, in its various matrices. In aquatic ecosystems, abundantly found in the Amazon region, this problem becomes more complex, because the high toxicity of some pesticides and their inappropriate use represent a great and potential risk of contamination of water bodies, an environment which, is, in most cases, the main final destination of pesticides applied in the crops. In this context, the main objective of this research is to estimate the potential risk of contamination by pesticides in surface waters in the Mojuí River sub-basin, in the Santarém micro-region in Baixo Amazonas, State of Pará. Studies of this nature help to identify possible areas susceptible to contamination by pesticides and, as these studies are scarce in this region, they are necessary and urgent for the implementation of policies aimed at protecting aquatic resources. The development of the work was carried out based on publicly available data about: toxicology (LC50) and physicochemical properties (half-life, water solubility, organic matter, sorption coefficient, among others) of the twenty-two (22) most used pesticides in the study area; and of data that characterize the landscape diversity of the Mojuí River sub-basin, such as altimetry data, land use and occupation, soil types, etc. As an important analytical tool, Geographic Information Systems (GIS) were used for the analysis and treatment of spatial data, as well as for the integration of different types of data, with the aid of Qgis 2.18 software. As a result of this work, a thematic risk map was obtained identifying the main areas subject to pesticide contamination in the study region. This map contains information that may be useful to direct future studies addressing the issue of pesticide contamination, as well as assisting in decision-making by water resource managers in this and other regions, given that such a methodology is robust and can be replicated to different regions respecting the environmental peculiarities of each location.
Keywords: Toxicologia; Contaminação; Recursos hídricos; Baixo Amazonas; CNPQ::CIÊNCIAS BIOLÓGICAS; Fisiologia Ambiental